A novel and facile route for the in situ formation of composites with dual coupling interactions for considerable millimeter wave absorption performance. Issue 37 (9th September 2021) - Liu, Chuyang; Jiang, Tao; Gao, Tian; Xia, Guangxian; Cao, Yufan; Fang, Gang; Peng, Kangsen; Zhang, Yanting; Zhang, Yujing; Zhu, Kongjun
Abstract : An in situ prepared BaZr x Fe12− x O19 /Fe3 O4 /BaZrO3 composite exhibits an outstanding millimeter wave absorption performance at around 35 GHz by gaining both the advantages of hard/soft magnetic exchange coupling and electromagnetic coupling. Abstract : A hard/soft magnetic exchange coupling or ferroelectric–ferromagnetic coupling has been proved to be beneficial for improving microwave absorption properties. Herein, we propose a BaZr x Fe12− x O19 /Fe3 O4 /BaZrO3 composite to integrate the advantages of the two couplings. However, the synthesis of BaFe12 O19 /Fe3 O4 in situ still remains a challenge due to the different degrees of oxidation resistance. In this work, by delicately exploiting the reducibility of graphene at high temperatures, the BaZr x Fe12− x O19 /Fe3 O4 /BaZrO3 composite was successfully prepared in situ by a hydrothermal process combined with a subsequent heat treatment at 600 °C. The two integrable couplings provide good impedance matching and attenuation characteristics for the material system, making it reach a considerable millimeter wave absorption performance around an atmospheric window of 35 GHz with a broad bandwidth of >7.36 GHz (32.64–40.00+ GHz) and a strong RL of −25.4 dB under an extremely thin thickness of 1.00 mm. The strategy provides a novel and facile pathway to design outstanding millimeter wave absorbers.